Chemical Aspects of Lesser Mouse Deer Meat (Jurnal Ilmu dan Teknologi Hasil Ternak, 2007)
An experiment aiming for studying chemical aspects of lesser mouse deer meat (Tragulus javanicus). This research explored the chemical aspects of lesser mouse deer meat (Tragulus javanicus). Eight lesser mouse deer (four female and four male) were used in chemical aspects of lesser mouse deer meat. The parameters observed included proximate analysis, amino acid, fatty acid, cholesterol and EPA-DHA of the meat. The results showed that average meat chemical composition were content of water, protein, fat, ash and cholesterol were 76.33 %, 21.42 %, 0.51 %, 1.20% and 50.00 mg/100 g, respectively. Fatty acid consist of lauric acid, miristate, palmitate, stearic, oleic, linoleic, and linolenic were 1.04 % 3.09%, 30.97, 0.77%., 59.41%, 3.22% and 1.12%, respectively. The total EPA and DHA was 0.13% and 0.05%, Â  Keywords: amino acid, fatty acid, cholesterol and EPA-DHA